COVID-19's Pathways of Impacts on Nutrition - Ruel, Marie T. (2020)
Marie Ruel POLICY SEMINAR Virtual Event - No backsliding: How can we re-orient food systems and health systems to protect nutrition and healthy diets in the context of COVID-19? Co-Organized by IFPRI and the CGIAR Research Program on Agriculture for Nutrition and Health (A4NH) MAY 28, 2020 - 09:30 AM TO 11:00 AM EDT